PENGARUH GUNCANGAN OUTPUT GAP DAN INFLASI TERHADAP SUKU BUNGA SEBAGAI SASARAN OPERASIONAL KEBIJAKAN MONETER DI INDONESIA - Utami Baroroh (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2012)
The objectives of this study are to observe interest rate response because shock/innovation of inflation and output gap. The data sample used in this study are quarterly time series data from 1983.1 – 2008.4. Those data are SBI interest rate, inflation (CPI) and output gap. A method of analysis in this study is Vector Error Correction Model (VECM). The empirical results of impulse response show that the effect of inflation and output gap shock to interest rate is positifDOI: 10.15408/sjie.v1i2.2601